Physician perspectives in the management of psoriasis and psoriatic arthritis: results from the population‐based Multinational Assessment of Psoriasis and Psoriatic Arthritis survey. (16th April 2015) - van de Kerkhof, P.C.M.; Reich, K.; Kavanaugh, A.; Bachelez, H.; Barker, J.; Girolomoni, G.; Langley, R.G.; Paul, C.F.; Puig, L.; Lebwohl, M.G.
Abstract Background Available literature on psoriasis and psoriatic arthritis (PsA) demonstrates a tremendous burden of disease and suggests underdiagnosis and undertreatment. Objective To obtain real‐world physician perspectives on the impact of psoriasis and PsA and its treatment on patients' daily lives, including perceptions of, and satisfaction with, current therapies. Methods The Multinational Assessment of Psoriasis and Psoriatic Arthritis (MAPP) surveyed dermatologists (n = 391) and rheumatologists (n = 390) in North America (Canada and the United States) and Europe (France, Germany, Italy, Spain and United Kingdom). Results Dermatologists classified 20.3% and 25.7% of their patients as having severe psoriasis and severe PsA respectively; rheumatologists indicated that 48.4% of their PsA patients had active disease. Of the psoriasis patients complaining of joint pain, only 33.0% had a diagnosis of PsA. An impact on daily activities or social/emotional well‐being was recognized by 57.2% to 79.3% of physicians. In patients with moderate‐to‐severe psoriasis, dermatologists reported 74.9% were receiving topical therapy, 19.5% conventional oral therapy and 19.6% biologics. Dermatologists and rheumatologists reported similar rates of topical (≈45%) and biologic (≈30%) therapy utilization for their PsA patients; conventional oral therapy was more often prescribed by rheumatologists (63.4%) vs. dermatologists (35.2%). Reasons for not initiating or maintaining systemic therapies were related to concerns about long‐term safety, tolerability, efficacy and costs (biologics). Conclusion Physicians in North America and Europe caring for patients with psoriasis and PsA acknowledge unmet treatment needs, largely concerning long‐term safety/tolerability and efficacy of currently available therapies; evidence suggests underdiagnosis of PsA and undertreatment of psoriasis among dermatologists.